Atypical traumatic hemipelvectomy - Nusspaumer, Federico; Vivas, Eudoxio; Garaza, Luis; Coronel de Grille, Alba (Cirugía del Uruguay, 1976)
A case of a severe abdominal-pelvic-crural wound, succesfully solved, is reportea. The interesting points of the treatment are remarked.